Applying biotechnology tools to improve control diseases of some tropical crops - Álvarez, E.; Llano Rodríguez, Germán Alberto; Loke, John Bernard; Mejía de los Ríos, J.F. (2004)
The application of biotechnology tools has made it possible to make significant advances in the detection of pathogens and in the study of the genetic variability of pathogen populations. As a result, adequate disease management strategies can be planned, and disease resistance markers for plants as well as DNA regions associated with resistance can be identified. Diseases, mainly those caused by microorganisms that cannot be cultivated in artificial media such as phytoplasmas, can be diagnosed using PCR. The bacterium Xanthomonas axonopodis pv. manihotis (Xam) can be identified using a specific probe and the identification of Ralstonia solanacearum in the soil is also facilitated by PCR. Species of Phytophthora can also be identified, phytoplasmas classified, and pathogen diversity established by using PCR-RFLP, thus improving the understanding of action mechanisms and how they co-evolve with the host. Other techniques such as RAPD, AFLP, and RAMS have made it possible to study the genetic variability of pathogens such as Sphaceloma manihoticola, Colletotrichum gloeosporioides, C. acutatum, Sphaerotheca pannosa, Ceratocystis paradoxa, and X. axonopodis pv manihotis. The identification of QTL markers associated with resistance to different species of Phytophthora in cassava has helped elucidate the genetics of resistance, whereas the identification of SSR markers associated with resistance to Xam is a tool that facilitates the selection of resistant genotypes. Functional genomics tools such as microarrays will give initial insight on the molecular basis of cassava’s defense response to X. axonopodis pv manihotis. Also, the identification of resistance genes and resistance gene analogs in cassava contributes to the genetic improvement of this crop. Biotechnology is evolving continuously, offering modern tools that help solve plant health problems.